Post-COVID Environmental Education in Morocco: School Clubs as Drivers of Student Engagement and Sustained Self-Reported Sustainable Practices - Riouch, Abderrahmane; Benamar, Saad; Ezzeri, Halima; Cherqi, Najat (International Journal of Environment, Engineering and Education, 2025)
Global environmental challenges, amplified by climate change, pollution, and socio-ecological inequities, emphasize the urgent need for educational systems that foster durable self-reported eco-responsible practices among youth. This study investigates whether participation in school-based environmental clubs enhances Moroccan secondary school students’ capacity to sustain such practices, specifically the responsible disposal of pandemic-related waste, awareness of vaccination-related medical waste risks, and water conservation within the post-COVID-19 context. A cross-sectional survey was conducted among 433 students (aged 15–19) from Fez, Sefrou, and Tangier, spanning urban and peri-urban contexts. Statistical analyses, including chi-square tests, two-way ANOVA, Principal Component Analysis (PCA), and K-means clustering, assessed the relationships between club membership, environmental knowledge, and self-reported practices. Results indicate that club members consistently reported higher self-reported eco-responsible practices (Cramer’s V = 0.20–0.22), with a mean practice score of 3.9 compared to 2.8 for non-members. PCA identified two engagement dimensions, Self-Reported Eco-Responsible Practices and Cognitive & Institutional Engagement, explaining 65.4% of total variance. Cluster analysis revealed three distinct profiles: Sustainably Engaged (25%), Latently Engaged (50%), and Unconcerned (25%). These findings confirm environmental clubs as pivotal drivers of sustained self-reported eco-responsible practices and awareness, despite territorial disparities, and support the integration of hybrid, health-oriented approaches to strengthen environmental education in underserved regions. This study highlights the critical role of school-based environmental clubs in fostering socio-ecological resilience, offering a scalable model for integrating public health and ecological sustainability into education systems, especially in post-crisis contexts.